Intraoperative High Frequency Ultrasound in Intracerebral High-Grade Tumors - Serra, C.; Stauffer, A.; Actor, B.; Burkhardt, J.-K.; Ulrich, N. H.-B.; Bernays, R.-L.; Bozinov, O. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: To demonstrate the utility of a new concept of intraoperative use of high frequency ultrasound (hfioUS) in maximizing the extent of resection (EOR) of intracerebral high-grade tumors.Materials and Methods: 22 Patients harboring an intracerebral high-grade tumor were retrospectively included in this study (14 primary tumors, 8 metastasis). 14 of them had a perilesional edema equal or greater to lesion volume, 3 had previously received radiotherapy. Following macroscopic tumor debulking, the small (11 × 31 mm) L15 – 7io (Philips, Bothell, USA) high-frequency probe (7 – 15 MHz) was introduced into the resection cavity and its walls were meticulously scanned to search for tumor remnants. Postoperative MR scan was evaluated by a board-certified independent neuroradiologist, who assessed the EOR.Results: Gross total resection was achieved in 21 patients (95.5 %). One patient had a small tumor remnant (6 × 4 × 3 mm) of a very large (80 × 60 × 74 mm) anaplastic astrocytoma, detected in the postoperative MR scan. A permanent postoperative hemiparesis was diagnosed in one patient with a metastasis in the motor area, while the other patients recovered without permanent neurological deficits from the surgery. Conclusion: The hfioUS probe allowed in this study a precise detection of the tumor and a detailed discrimination between normal, pathological and edematous tissue in all 22 cases.
Keywords: brain; tumor; intraoperative; ultrasound